Improving Deep Sensitivity of Four-Electrode Focused Impedance Method In Lungs by Varying Electrode Geometries - Mobarak, Mahjabin; Rabbani, K Siddique e (Bangladesh Journal of Medical Physics, 2022)
Bio-Electrical impedance is of special interest in the detection and diagnosis of lung problems, particularly in the low and medium income countries. An age old simple technique employing four electrodes is known as ‘Tetra Polar Impedance Measurement (TPIM)’ but it cannot localize a particular zone of interest region. A new technique named as ‘Focused Impedance Method (FIM)’ was innovated by a Dhaka University group which gives high sensitivity in a localized zone of interest. Previously FIM was used from one side of the thorax which gave a rather limited information from the lungs, from shallow depths only. In order to get information from deeper regions of the lungs a new configuration of electrodes for FIM was proposed by the same group at Dhaka University which placed two electrodes at the front and two electrodes at the back of the thorax in a horizontal plane. It is expected that the degree of depth sensitivity would depend on electrode separation on both the sides. The electrode width may also have an effect. In order to study these quantitatively, COMSOL Multiphysics software was used to simulate the measurements in a rounded rectangular volume to represent a typical thorax, which was filled with isotonic saline. Electrode separations of 5cm, 10cm, 15cm and 20cm were studied while electrode widths studied were 0.15cm, 1cm and 3cm. The work supported the proposed new configuration of electrodes for FIM in that this method gives enhanced sensitivity throughout the depths of a lung and that for a thorax with a cross section of 33cm26cm, an electrode separation between 10cm and 15cm would give optimum results. For electrode width, the ones studied did not give any significant difference, however, the smallest (0.15cm) one appeared to give slightly better results. Bangladesh Journal of Medical Physics Vol.15 No.1 2022 P 43-54